Apa yang Mendorong Pengguna Untuk Mengadopsi Centralized Exchange (CEX)? Tinjauan Literatur Sistematis Menggunakan Metode PRISMA - Steven, Liauwnad; Lisana, Lisana (Universitas Gunadarma, 2025)
Centralized Exchanges (CEX) are intermediaries managed by centralized entities, offering a secure and user-friendly platform for cryptocurrency trading. Despite the rapid adoption of CEXs, particularly in Indonesia a systematic understanding of the factors influencing users’ intention to use these platforms remains limited. This study conducts a Systematic Literature Review (SLR) to identify, classify, and analyze the behavioural intention factors toward CEX usage from 2015 to 2025. Utilizing the PRISMA 2020 framework, the review integrates articles sourced from Scopus, PubMed, and Web of Science using a validated combination of keywords. A total of 27 relevant studies were identified after applying inclusion and exclusion criteria. The analysis reveals a growing body of research interest starting from 2018 and keep growing until now, with a concentration of studies in Asia, particularly in China and India. Most studies apply established models such as Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), and Theory of Planned Behaviour (TPB). This systematic review identified that the predominant factors explored across studies are risk perception, trust, awareness, ease of use, and users' attitudes. However, research gaps remain in areas such as emotional experience, social influence, and regulatory context across various geographical regions. This literature review provides a comprehensive mapping of current research distributions and proposes directions for future exploration in the domain of centralized cryptocurrency exchanges